Correlation between Ball Games and Fundamental Motor Skill of 4-5 Years Old Children at Jebres, Surakarta - Anastasia Lucky Aurelia; Warananingtyas Palupi; Novita Eka Nurjanah (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2021)
The present study aimed to examine the relationship between ball games and thefundamental motor skill of 4-5 years old children. Taking place in 4 kindergartensin Surakarta, a correlational study was applied. The participants were the parentsor guardians of 4-5 years old children (n=86). The data were collected by distributing questionnaires and conducting interviews with parents. Prior to data analysis, normality, linearity, and hypothesis tests were performed. The result of the normality test showed a significance value of 0.200 0,05. While the significance of linearity was 0.174 0.05, which indicates a relationship between the two variables being studied. The hypothesis test result with analysis Pearson showed a significance value of 0,0000,05, indicating that there is a relationship between the ball games and the fundamental motor skill of 4-5 years old children. The correlation of the two variables was categorized as very strong, indicated by the correlation coefficient of 0.895